TRIM16 transcription factor in prostate cancer - L. V. Spirina; A. К. Gorbunov; I. V. Kondakova; E. М. Slonimskaya; Е. A. Usynin; N. V. Tarasenko (Бюллетень сибирской медицины, 2018)
The aim of this investigation was to reveal the expression TRIM16, ERα, ERβ and AR in prostate cancer tissues compared to benign hyperplasia and clinical and morphological parameters.Materials and methods. Fifty patients with locally advanced prostate cancer with T2-3N0M0 and twenty patients with benign hyperplasia were included in the study. Prostate cancer patients were divided into subgroups according the Gleason score. Nine patients had Gleason score of 6, eighteen patients had 7 Gleason score, seven patients got 8 Gleason score and seven patients got 9 Gleason score. PSA level was from 4 to 100 ng/ml. TRIM16, ERα, ERβ and AR expression was determined by PCR in real time.Results. Increase of TRIM16 expression in prostate cancers was accompanied by high AR and ERα expression. The onco-suppressor ERβ was not changed in cancer tissues compared to benign hyperplasia. The Gleason score level was dependent on AR/ERβ relation. Associations between the PSA, AR, ERβ and TRIM16 were found in prostate cancersConclusion. Transcription factor TRIM16 participated in prostate cancer development. The connection between the ER and AR expression and clinical and morphological factors was found.